Caspase-8 in endothelial cells maintains gut homeostasis and prevents small bowel inflammation in mice - Tisch, Nathalie; Mogler, Carolin; Stojanovic, Ana; Luck, Robert; Korhonen, Emilia Anne; Ellerkmann, Alexander; Adler, Heike; Singhal, Mahak; Schermann, Géza; Erkert, Lena; Patankar, Jay V; Karakatsani, Andromachi; et al. (EMBO molecular medicine, 2022)
The gut has a specific vascular barrier that controls trafficking of antigens and microbiota into the bloodstream. However, the molecular mechanisms regulating the maintenance of this vascular barrier remain elusive. Here, we identified Caspase-8 as a pro-survival factor in mature intestinal endothelial cells that is required to actively maintain vascular homeostasis in the small intestine in an organ-specific manner. In particular, we find that deletion of Caspase-8 in endothelial cells results in small intestinal hemorrhages and bowel inflammation, while all other organs remained unaffected. We also show that Caspase-8 seems to be particularly needed in lymphatic endothelial cells to maintain gut homeostasis. Our work demonstrates that endothelial cell dysfunction, leading to the breakdown of the gut-vascular barrier, is an active driver of chronic small intestinal inflammation, highlighting the role of the intestinal vasculature as a safeguard of organ function.
Gesehen am 12.02.2024